Participation in continuous professional development: exploring views of social workers in the Johannesburg child protection field - Myaka, Busisiwe (My University, 2022)
The South African Council of Social Service Professions (SACSSP) developed a policy to encourage social workers to participate in continuous professional development (CPD). The CPD policy was aimed at ensuring that skills of social workers are adequately improved and promotes further development of the profession. Social work is a profession that tasked with ensuring the wellbeing of those in need and who cannot protect themselves such as children. As a result it becomes highly necessary for child protection social workers to improve on their knowledge base to ensure quality of services provision. The study was exploratory in nature and aimed to discover what the views of social workers in the child protection sector in the Johannesburg area were on CPD and whether or not they are actively engaged in CPD activities. Qualitative research methods were applied in data collection and analysis of research findings. The research design was a case study in order to better understand the phenomenon investigated. Semi-structured interviews were conducted with a population of twelve social workers who were in the child protection field along with four key informants. The findings of the research study indicated some understanding and value of CDP as an important aspect of training and development for child protection social workers in practice. The study highlighted the types of CPD child protection social workers were engaged in as well as the impact of the child protection organisations they find themselves in. Further education on the importance of CPD participation should take place within organisations and the introduction of an occupational social worker would play an essential role in improving child protection social workers engagement in CPD.
A research project submitted in partial fulfilment of the requirements for the degree Master of Arts in Social Work to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2022